2013
DOI: 10.1111/bph.12305
|View full text |Cite
|
Sign up to set email alerts
|

Levels of heroin and its metabolites in blood and brain extracellular fluid after i.v. heroin administration to freely moving rats

Abstract: BACKGROUND AND PURPOSEHeroin, with low affinity for μ-opioid receptors, has been considered to act as a prodrug. In order to study the pharmacokinetics of heroin and its active metabolites after i.v. administration, we gave a bolus injection of heroin to rats and measured the concentration of heroin and its metabolites in blood and brain extracellular fluid (ECF). EXPERIMENTAL APPROACHAfter an i.v. bolus injection of heroin to freely moving Sprague-Dawley rats, the concentrations of heroin and metabolites in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 45 publications
4
79
0
Order By: Relevance
“…Previous work in our laboratory has shown that 6-MAM is the predominating metabolite in brain and blood after subcutaneous and intravenous heroin administration in mice and rats, respectively, indicating that 6-MAM is the main contributor to acute heroin effects Gottås et al, 2013). In addition, the psychomotor-stimulating effect and dopamine peak levels coincided with the rising concentration of 6-MAM in brain tissue, at a time when heroin was no longer detectable Gottås et al, 2013Gottås et al, , 2014. Furthermore, pharmacokinetic studies have indicated that heroin is mainly metabolized outside the brain .…”
Section: Introductionmentioning
confidence: 90%
“…Previous work in our laboratory has shown that 6-MAM is the predominating metabolite in brain and blood after subcutaneous and intravenous heroin administration in mice and rats, respectively, indicating that 6-MAM is the main contributor to acute heroin effects Gottås et al, 2013). In addition, the psychomotor-stimulating effect and dopamine peak levels coincided with the rising concentration of 6-MAM in brain tissue, at a time when heroin was no longer detectable Gottås et al, 2013Gottås et al, , 2014. Furthermore, pharmacokinetic studies have indicated that heroin is mainly metabolized outside the brain .…”
Section: Introductionmentioning
confidence: 90%
“…Extrapolation of rat data to humans is made more difficult for heroin because the main active components are its metabolites 6-AM and morphine. These metabolites are formed at different rates in humans compared with rodents (Comer et al, 1999;Rentsch et al, 2001;Gottås et al, 2013) and their rates of distribution to brain may also differ. These considerations underscore the need to advance opioid vaccines to human studies to properly assess their therapeutic potential.…”
Section: Efficacy Of Vaccines For Opioid Use Disordersmentioning
confidence: 99%
“…Drug exposure can be measured using an animal model by microdialysis at the target site (Gottås et al, 2013). Because the dialysate contained a considerable amount of nonvolatile salts, the ionization of analytes would be suppressed when microdialysate was directly analyzed by UPLC-MS/MS without prior sample preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous monitoring of brain monoamine level changes by the in vivo microdialysis sampling technique is an important tool in the discovery of new drug therapies for a large number of neurologic disorders, such as Parkinson's disease, Alzheimer's disease, epilepsy, and neuropsychiatric disorders (Garrison et al, 2002). The advantages of the microdialysis technique include not only simultaneous sampling at multiple sites, such as the brain (Gottås et al, 2013), but also that there is no need for sample preparation because the dialysis membrane excludes proteins from the aqueous sample (Tsai, 2003). The use of ionpair high-performance liquid chromatography-electrochemical detection (HPLC-ECD) is of great interest for the determination of monoamine neurotransmitters [i.e., norepinephrine; epinephrine; 3,4-dihydroxyphenylacetic acid (DOPAC); DA; 5-hydroxyindole-3-acetic acid (5-HIAA); homovanillic acid (HVA); 5-HT; and 3-methoxytyramine hydrochloride] in microdialysis samples (Bicker et al, 2013).…”
Section: Introductionmentioning
confidence: 99%